Keihlasan dan Arti Pentingnya Dalam Mengelola Pendidikan - Ni'mawati Ni'mawati; Andewi Suhartini; Nurwadjah Ahmad E Q (STAI AL-FALAH CICALENGKA, 2020)
This paper is motivated by the concept of sincerity associated with the management of educational institutions to form professional educators and education personnel. Sincerity as the teachings of the Islamic religion are contained in the Qur'an and hadith, what is the definition and nature of sincerity, what are the characteristics of sincere people and how is the implementation of sincerity in managing educational institutions. By using a qualitative research approach and descriptive analysis method with data sources in the form of verses of the Qur’an, the hadith of the prophet and the results of research by experts, it was found that the following were: 1) the nature of sincere is pure in intention, clean in mind in doing good, upright in heart act and do only hoping to please Allah. 2) the characteristic of sincere people is that they always do good deeds and are sincere in doing good deeds; awake from everything that Allah forbids; in working, doing activities, teaching, educating and managing educational institutions; someone who does it sincerely will feel happy if goodness is realized by anyone, and 3) the management of educational institutions sincerely has an impact on the formation of professional educators and educational staff.Keyword: sincerity, managing and educational institutionsAbstrakTulisan ini dilatarbelakangi oleh konsep ikhlas dihubungkan dengan pengelolaan lembaga pendidikan untuk membentuk pendidik dan tenaga kependidikan yang profesional. Ikhlas sebagai ajaran agama islam terdapat dalam Al Qur’an dan hadis, bagaimana definisi dan hakikat ikhlas, bagaimana karakteristik orang-orang yang ikhlas dan bagaimana implementasi ikhlas dalam mengelola lembaga pendidikan. Dengan menggunakan pendekatan penelitian kualitatif dan metode deskriptif analisis dengan sumber data berupa ayat-ayat alquran, hadis nabi dan hasil penelitian para ahli, ditemukan hal-hal sebagai berikut: 1) hakikat ikhlas adalah suci dalam niat, bersih batin dalam beramal, lurus hati dalam bertindak dan berbuat hanya mengharapkan ridha Allah. 2) karakteristik orang ikhlas adalah senantiasa beramal dan bersungguh-sungguh dalam beramal; terjaga dari segala yang diharamkan Allah; dalam bekerja, beraktivitas, mengajar, mendidik, dan mengealola lembaga pendidikan; seseorang yang meakukannya dengan ikhlas akan merasa senang jika kebaikan terealisasi oleh siapapun, dan 3) pengelolaan lembaga pendidikan dengan ikhlas berdampak pada terbentuknya pendidik dan tenaga kependidikan yang profesional.Kata kunci: Ikhlas, mengelola dan lembaga pendidikan